Examining the effectiveness of gamification as a tool promoting teaching and learning in educational settings: a meta-analysis - Li, Minzi; Ma, Siyu; Shi, Yuyang (Frontiers in Psychology, 2023)
The integration of gamification into educational settings has gained recognition for its potential to boost student motivation, engagement, interest, and learning outcomes. Despite its popularity, research on gamification has produced mixed results regarding student learning outcomes. This meta-analysis aims to synthesize the existing empirical evidence on the effectiveness of gamification as a tool for promoting teaching and learning in educational settings. Forty-one studies with 49 independent samples involving more than 5,071 participants were included in our analysis. Results from random effects models showed an overall significant large effect size (g = 0.822 [0.567 to 1.078]). The research performed the moderator analysis to scrutinize the effects of a number of factors on the relationship between gamification and student learning outcomes. The study uncovered significant moderating effects for user type, educational discipline, design principles for educational gamification, duration of “gameful” experience, and learning environment. However, measurement of student outcomes and publication type did not appear to have any significant moderating effect. Those findings hold important implications for improving and implementing gamification to promote teaching and learning in future research.